Biologically inspired region of interest selection for low bit-rate video coding - Tsapatsoulis, Nicolas; Pattichis, Constantinos S.; Rapantzikos, Konstantinos (My University, 2007)
A variety of approaches have been proposed in the literature for region-of-interest (ROI) estimation. In most of them the ROI definition is highly subjective, i.e., lacks scientific evidence in supporting the claim that the areas defined as ROIs are indeed perceptually interesting. In this paper we attempt to model ROIs as the visually attended areas indicated by a saliency map in order to lower as much as possible the subjectivity of selection. For evaluation purposes we follow a ROI-based video compression setup and present comparisons with state-of-the-art algorithms in terms of perceived visual quality and video compression improvement. Extended experiments concerning both MPEG-1 as well as low bit-rate MPEG-4 video encoding were conducted showing significant improvement in video compression efficiency without perceived deterioration in visual quality
Keywords: Image processing; Imaging systems; Visual communication